Pengelolaan Manajemen Kurikulum Pembelajaran Bahasa Arab Di Madrasah Aliyah Al-Amiriyyah Blokagung Banyuwangi - Nawawi, Mahbub; Ulya, Inayatul (Universitas KH. Mukhtar Syafaat, 2024)
This research aims to determine the management of the Arabic language learning curriculum at Madrasah Aliyah Al Amiriyyah Blokagung Banyuwangi. This type of research uses qualitative research methods. Data collection is through observation, interviews and documentation. With key informants, namely the school principal, Arabic language studies teacher, and curriculum supervisor. And data validity techniques use triangulation. The data analysis used goes through several stages, namely data reduction, data presentation, and drawing conclusions/verification. The results of this research begin with planning the management of the Arabic language learning curriculum by making lesson plans, syllabi, making prota (annual programs) and promes (semester programs) and in the planning involving existing stechholders; organizing management of the Arabic language learning curriculum, namely by teachers participating in MGMP (Subject Teachers' Conference) activities; Meanwhile, the implementation of Arabic language learning curriculum management is carried out by all sectors in Madrasah Aliyah Al Amiriyyah Blokagung Bnayuwangi with the aim of implementing Arabic language learning curriculum management to be carried out in accordance with the stated objectives; and evaluation of Arabic language learning curriculum management consists of three types of evaluation, namely in terms of character, spiritual and social. And in carrying out the evaluation, it is measured from the value of the material presented.